Cerebrotendinous xanthomatosis: clinical and MRI study (a case report). Issue 1 (January 1990) - Fiorelli, M; Di Piero, V; Bastianello, S; Bozzao, L; Federico, A
Abstract : We report a patient with cerebrotendinous xanthomatosis (CTX) presenting with dementia, spastic tetraparesis and an unreported akinetic-rigid syndrome. Computed tomography (CT) showed only cerebellar abnormalities while magnetic resonance imaging (MRI) detected additional pallidal and mesencephalic focal alterations. MRI findings, but not CT, correlated with the clinical picture.